Bioinformatics : a practical guide to the analysis of genes and proteins - Baxevanis, Andreas D; Ouellette, B. F. Francis (Wiley, 1998)
BIOINFORMATICS, a field integrating molecular biology and computational methods, has revolutionized gene discovery and related research. This new, rapidly evolving discipline provides the tools scientists need to cope with the flood of biological data and raw DNA and protein sequence information generated by such endeavors as the Human Genome Project. Bioinformatics: A Practical Guide to the Analysis of Genes and Proteins makes computational biology accessible to scientists at all levels of expertise, including those with no formal computer training. It cuts through the overwhelming array of existing tools and databases, helping the reader design and implement a successful sequence analysis strategy. Presented by leading authorities in computational biology, this edited volume covers the gamut of topics, from using software and Internet resources to submitting DNA sequences to databases. Other topics include: * The GenBank sequence database and structure databases * Sequence analysis using GCG * Information retrieval from biological databases * The NCBI data model * Sequence alignment and database searching * Practical aspects of multiple sequence alignment * Phylogenetic analysis * Predictive methods using nucleotide sequences and protein sequences * Navigating public physical mapping databases * ACeDB: A database for genome information Bioinformatics is fully referenced and provides appendices, sample sequence file formats, and over 120 illustrations. A must have for molecular biologists, geneticists, and any biologist interested in genes and proteins, it can also be used in a one-semester practical course on sequence analysis and bioinformatics.
Methods of biochemical analysis ; v. 39
Keywords: sekvence aminokyselin; Clinical Laboratory Techniques; klinické laboratorní techniky; sekvence nukleotidů; biomedicínské inženýrství; databáze genetické; lékařská informatika; Amino Acid Sequence; Base Sequence; Databases, Genetic; Laboratorní technika; sekvenční analýza; Computational Biology; Sequence Analysis; výpočetní biologie